2013
DOI: 10.5032/jae.2013.01124
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Effects of a Math-Enhanced Agricultural Teaching Methods Course

Abstract: Numerous calls have been made for agricultural education to support core academic subject matter including mathematics. Previous research has shown that the incorporation of mathematics content into a teaching methods course had a positive effect on preservice teachers' mathematics content knowledge. The purpose of this study was to investigate the effects of a math-enhanced agricultural education teaching methods course on preservice agricultural education teachers' mathematics ability, personal mathematics e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 37 publications
4
17
1
Order By: Relevance
“…The researchers discovered preservice teachers in their final year of a teacher education program were efficacious in personal mathematics efficacy and personal teaching efficacy and moderately efficacious in mathematics teaching efficacy, which is also consistent with Jansen and Thompson (2008). Furthermore, Stripling and Roberts (2013a) reported Florida preservice agricultural education teachers were efficacious in personal mathematics efficacy and personal teaching efficacy and moderately efficacious in mathematics teaching efficacy, and this finding is in agreement with Jansen and Thompson (2008) and Stripling and Roberts (2012a). Additionally, Stripling and Roberts (2013a) investigated the effects of a mathenhanced teaching methods course on personal mathematics efficacy, mathematics teaching efficacy, and personal teaching efficacy.…”
Section: Agricultural Educators' Mathematics Selfefficacysupporting
confidence: 73%
See 1 more Smart Citation
“…The researchers discovered preservice teachers in their final year of a teacher education program were efficacious in personal mathematics efficacy and personal teaching efficacy and moderately efficacious in mathematics teaching efficacy, which is also consistent with Jansen and Thompson (2008). Furthermore, Stripling and Roberts (2013a) reported Florida preservice agricultural education teachers were efficacious in personal mathematics efficacy and personal teaching efficacy and moderately efficacious in mathematics teaching efficacy, and this finding is in agreement with Jansen and Thompson (2008) and Stripling and Roberts (2012a). Additionally, Stripling and Roberts (2013a) investigated the effects of a mathenhanced teaching methods course on personal mathematics efficacy, mathematics teaching efficacy, and personal teaching efficacy.…”
Section: Agricultural Educators' Mathematics Selfefficacysupporting
confidence: 73%
“…In an effort to improve the mathematics ability of preservice agricultural education teachers, Stripling and Roberts (2013a) investigated the effects of a math-enhanced teaching methods course on mathematics ability. Stripling and Roberts reported a 12.15% increase in mathematics ability scores after the math-enhanced teaching methods course.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, the participants averaged 26.5% on the mathematics ability instrument, which indicated the preservice teachers were not proficient in solving agricultural mathematics problems. This disconnect between mathematics efficacy and mathematics ability is consistent with prior research (Stripling & Roberts, 2012a, 2012b, 2013a, 2013b and supports the use of the sample.…”
Section: Target Population and Samplesupporting
confidence: 72%
“…Four studies (Stripling & Roberts, 2012a, 2013a, 2013b, 2013c were found in the agricultural education literature related to mathematics efficacy and mathematics teaching efficacy. Stripling and Roberts (2012a, 2013a, 2013b found preservice teachers at the University of Florida were efficacious in personal mathematics efficacy and moderately efficacious in mathematics teaching efficacy. Furthermore, Roberts (2013a, 2013b) found the incorporation of mathematics teaching and integration strategies based on the Math-in-CTE model (Stone, Alfeld, Pearson, Lewis, & Jensen, 2006) into an agricultural education teaching methods course did not significantly affect mathematics efficacy or mathematics teaching efficacy.…”
Section: Preservice Agricultural Education Teachersmentioning
confidence: 99%
See 1 more Smart Citation